Testing and modelling the in-plane seismic response of clay brick masonry walls with boundary columns made of precast concrete interlocking blocks. (15th January 2017) - Wang, Guojue; Li, Yingmin; Zheng, Nina; Ingham, Jason M.
Highlights: Two new kinds of fabricated concrete columns have been designed and these kinds of columns can be assembled by hand. The basic performance of the columns has been examined in experiments. The modelling method of masonry has been investigated, and the models have been verified by experimental results. More models have been created for further analysis. Abstract: Post-earthquake evidence indicates that traditional rural masonry structures in China do not perform well when subjected to large intensity ground shaking. Because common cast-in-place (CIP) reinforced concrete (RC) construction is relatively expensive for many rural people the construction technique is currently unpopular in rural areas of China. In comparison, the assembly of precast concrete interlocking blocks to form fabricated columns is cost effective and easy to construct using available resources, and implementation of the technique in rural masonry structures will result in superior seismic behavior. To address these issues a study was undertaken to experimentally establish the performance of masonry walls with traditional concrete columns and with fabricated boundary columns constructed of precast concrete interlocking blocks, and finite element models were generated to extend the range of parameters considered in the study. It was established that the implementation of fabricated concrete boundary columns made of precast concrete interlocking blocks improved seismic response with respect to traditional construction practice and 37 trial buildings were constructed to demonstrate implementation of the technique. It was also established that computational models could be generated to adequately replicate laboratory observations, endorsing use of this method to extend the project scope.